"Breestraat 73" Middelburg. (Middelburg : Breestraat 73, 1981)
Zembsch, Jan ; de Regt, Adriaan ; Verstraeten, William ; Hoogendoorn, Pieter ; v.d. Ven, Jace ; v. Kerwijk, Joke ; v.d. Vliet, Paul ; Dieleman, Piet ; Pingen, Bob ; Moonen, Fons ; Poth, Uwe ; de Jonge, Ko ; Popgroep Booster ; Cornelissen, Johan ; Kappetein, Johan ; de Graaf, Lucy ; Wouters, Joop ; Ventura, Julia
"Breestraat 73" Middelburg, een projekt van mei 1980 tot en met mei 1981.
boek